คุณภาพชีวิตการทำงานของบุคลากรเทศบาลตำบลบ้านตาก - ณัฐฐิณี เวียงไชย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objective of this independent study was to study personnel’s opinions towards quality of work life at Ban Tak Subdistrict Municipality. The study was based on the working life quality concept by Walton. Questionnaire, as a study tool, were distributed to 122 personnel. All derived data was analyzed by descriptive statistics consisting of frequency, percentage, means and standard deviation. The results of the study showed that most respondents were male (54.92 %), married (58.20 %), 31 – 40 years old (38.52 %), with high school education or equivalent (27.05 %), had less than 11 years of working (79.51 %), were temporary employees (65.57 %) and earned less than 10,000 Baht per month (67.21 %). The overall quality of work life of personnel in Ban Tak Subdistrict Municipality was at the moderate level, at 3.12 points of a total of 5. Considering all aspects of quality of work life, the employees ranked life pace at the high level, while social relevance, constitutionalism, development of human capacities, social integration, growth and security, adequate and fair compensation, safe and healthy environment were ranked at the moderate level. From the study of personal factors that affected the quality of work life, it was found that employees with different marital status and salary had different opinion on quality of work life.